2006
DOI: 10.1002/cne.21095
|View full text |Cite
|
Sign up to set email alerts
|

Severe alcohol‐induced neuronal deficits in the hippocampus and neocortex of neonatal mice genetically deficient for neuronal nitric oxide synthase (nNOS)

Abstract: Alcohol can severely damage the developing brain, and neuronal loss is a critical component of this injury. Thus, identification of molecular factors that ameliorate alcohol-induced neuronal loss is of great importance. Previous in vitro work has demonstrated that nitric oxide (NO) protects neurons against alcohol toxicity. We tested the hypothesis that neonatal mice carrying a null mutation for neuronal nitric oxide synthase (nNOS), the enzyme that synthesizes NO in neurons, have an increased vulnerability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 119 publications
0
28
0
Order By: Relevance
“…Apoptotic death of selected cell populations is a commonly observed pathogenic feature of ethanol-induced teratogenesis in both in vivo and in vitro model systems (3,7,11,14,37,40). Among the proposed mechanisms underlying ethanol-induced apoptosis and malformation is oxidative stress.…”
mentioning
confidence: 99%
“…Apoptotic death of selected cell populations is a commonly observed pathogenic feature of ethanol-induced teratogenesis in both in vivo and in vitro model systems (3,7,11,14,37,40). Among the proposed mechanisms underlying ethanol-induced apoptosis and malformation is oxidative stress.…”
mentioning
confidence: 99%
“…Several previous studies have shown that neuronal losses induced by alcohol are greater in nNOS−/− mice than in wild type (Bonthius et al, 2002; 2006; de Licona et al, 2009). However, in all of those studies, neuronal numbers were determined in infant mice, immediately following the alcohol exposure.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously reported that genetic deficiency of nNOS worsens alcohol-induced microencephaly and neuronal loss both in vitro and in developing mice (Bonthius et al, 2002;Bonthius et al, 2006). This suggested that nNOS exerts a neuroprotective effect against alcohol toxicity.…”
Section: Transduction Of the Nnos Gene Via An Ad5-nnos Viral Vector Pmentioning
confidence: 95%
“…Based on our previous observation that nNOS protects CGN cultures against alcohol-induced cell death (Bonthius et al, 2002) and that nNOS−/− mice have an enhanced vulnerability to alcohol-induced microencephaly and neuronal loss (Bonthius et al, 2002;Bonthius et al, 2006), we hypothesized that delivery of the nNOS gene into CGN derived from nNOS−/− mice could protect the neurons against alcohol toxicity. The results confirmed this hypothesis.…”
Section: Transduction Of the Nnos Gene Into Cultured Cgn With Ad5-nnomentioning
confidence: 99%